Identifikasi dan Penetapan Kadar Rhodamin B pada Terasi yang Dijual di Pasar Ciawitali Kabupaten Garu - Mamay Mamay; Acep Gunawan (STIKes Karsa Husada Garut, 2017)
Some synthetic dyes increasingly used by public along with the development of science and technology. Rhodamin B is one of synthetic dyes commonly used in textile and paper industry. However, the dye is often misused in food use. According to the Regulation of Minister of Health No. 33 of 2012 states that Rhodamin B is a prohibited Food Additives. Terasi is a food wich made from shrimp that is often found in the market by using red food color additives. The worries of using Rhodamine B used in terasi wich sold in Ciawitali Market of Garut Regency are the background of this research. Therefore, identification and determination of Rhodamine B on terasi wich sold in those markets. A laboratory descriptive method was used in this study, which illustrated the presence and Rhodamine B content in the terasi samples. To identify the presence of Rhodamin B contained in terasi, a qualitative test was used thin layer chromatography (TLC) method. To determine concentration of Rhodamin B in terasi, a quantitative test used UV-Vis Spectrophotometry with wavelength 554 nm. From the research results obtained from five samples of terasi found four samples of red terasi contain Rhodamin B. The value of Rhodamine B in samples 1 to 4 each as much as 222.5 mg / kg; 201.9 mg / kg; 57.55 mg / kg and 72.6 mg / kg. Based on the results of this study, red terasi wich sold on the market Ciawitali contain Rhodhamin B with various levels and suggested to the public should be careful to buy the red terasi.